Teenage Pregnancy and Associated Risk Factors and Outcome in Nepal From 2000-2020: A Systematic Review and Meta-Analysis - Shrestha, D. B.; Budhathoki, P.; Shrestha, O.; Karki, S.; Thapa, N.; Dangal, G.; Baral, G.; Itani, S.; Poudel, A. (Kathmandu University Medical Journal, 2022)
Background Teenage pregnancy is considered a high-risk pregnancy in terms of reproductive outcome and the subsequent financial constraint. Objective To assess the prevalence of teenage pregnancy, associated risk factors, and outcomes in the context of Nepal. Method We searched electronic databases to search relevant articles published from January 2000 till October 2020 using the keywords with appropriate Boolean operators. All the data were extracted into a standardized form designed in Excel. We conducted a statistical analysis using Comprehensive Meta-Analysis Software (CMA) version 3. Data pooled for proportion with 95% confidence interval (CI). A Forest plot was used to visualize the degree of variation between studies. Result Fourteen studies were included in the analysis after the rigorous screening of 4425 studies. Prevalence of teenage pregnancy was 13.2% (Proportion, 0.132; CI, 0.077- 0.215). Among teenage pregnancies, 11.8% were already multigravida (Proportion, 0.118; CI, 0.029-0.374). Among teen pregnancies, 18.6% were illiterate; among the literate, only 25.9% were of education above grade 10,31.9% were unaware of contraceptive methods, and only 3.2% reported using any contraception methods. 75.4% of teenage pregnancies had a vaginal delivery with or without episiotomy, 6.5% by instrumental deliveries, and 21.5% by cesarean section. Preterm delivery was 12.0%, and post-term delivery was 8.2%. Abortion was reported in 11.1% of teenage pregnancies. Major tears were reported in 52.9%, obstructed labor was in 4%, and pre-labor rupture of the membrane was in 7.0% of teenage pregnancies. The low birth weight of newborns was 19.4%. Stillbirth and neonatal deaths were 1.7% and 1.4%, respectively. Conclusion The prevalence of teenage pregnancy in Nepal was 13.2%. The majority of them did not use any form of contraceptives; and had low education. Several maternal and neonatal complications were reported among teenage pregnancies.